PENGEMBANGAN SKENARIO PEMBELAJARAN TEKS NARASI DENGAN MODEL DISCOVERY LEARNING UNTUK SISWA SMP KELAS VII - Yani, Rindu Rima; Ariyani, Farida; Rusminto, Nurlakasana Eko (FKIP Universitas Lampung, 2020)
AbstractThe problem of this research is how to develop a learning scenario by using discovery learning model to the seventh grade students of Junior High School. The method that is used in this reasearch is R and D (Research and Development) which reffered to Borg and Gall. They states that the development procedures use five stages : collecting information, design arrayment, design validity, design revision, and final product. The results of this research and development are in the form of narrative text learning scenarios using discovery learning models for seventh grade junior high school students who have been declared fit for use by material experts with a percentage of 78% with very feasible categories, the feasibility aspect of the presentation obtains a 75% percentage with the proper category and feasibility aspects language percentage of 75% with a decent category.Keywords: narrative text learning scenarios, discovery learning models, SMPMasalah dalam penelitian ini ialah bagaimanakah pengembangan skenario pembelajaran menggunakan model discovery learning untuk siswa SMP kelas VII. Tujuan Penelitian ini ialah menghasilkan sebuah produk berupa skenario pembelajaran menggunakan model discovery learning untuk materi teks narasi di SMP. Metode dalam penelitian ini ialah Research and Development (R D) mengacu prosedur pengembangan Borg dan Gall dengan menggunakan lima tahap, yaitu pengumpulan informasi, perancangan desain, validitas desain, revisi desain, dan produk akhir. Hasil penelitian dan pengembangan ini berupa sebuah skenario pembelajaran teks narasi menggunakan model discovery learning untuk siswa SMP kelas VII yang telah dinyatakan layak digunakan oleh ahli materi dengan presentase 78% dengan kategori sangat layak, aspek kelayakan penyajian memperoleh presentase 75% dengan kategori layak dan aspek kelayakan bahasa presentase 75% dengan kategori layak.